2021
DOI: 10.3346/jkms.2021.36.e223
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage due to Thrombosis with Thrombocytopenia Syndrome after Vaccination against COVID-19: the First Fatal Case in Korea

Abstract: Vaccination with an adenoviral vector vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can result in the rare development of thrombosis with thrombocytopenia mediated by platelet-activating antibodies against platelet factor 4 (PF4). This is a life-threating condition that may be accompanied by bleeding due to thrombocytopenia with thrombosis of the cerebral venous sinus or splanchnic vein. Herein, we describe the first fatal case of thrombosis with thrombocytopenia syndrome in Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Wolf et al ( 106) reported 3 cases of CVT after COVID-19 vaccination who were successfully treated by endovascular rheolysis. Although the outcome of EMT in the case report by Choi et al (105) was not satisfactory, they suggested that if the EMT is done at early stages, and before the beginning of cortical venous occlusion, the outcome might be better. Therefore, if VITT-associated CVT is clinically suspected and the symptoms deteriorate quickly, early EMT intervention is necessary (105).…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 91%
See 2 more Smart Citations
“…Wolf et al ( 106) reported 3 cases of CVT after COVID-19 vaccination who were successfully treated by endovascular rheolysis. Although the outcome of EMT in the case report by Choi et al (105) was not satisfactory, they suggested that if the EMT is done at early stages, and before the beginning of cortical venous occlusion, the outcome might be better. Therefore, if VITT-associated CVT is clinically suspected and the symptoms deteriorate quickly, early EMT intervention is necessary (105).…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 91%
“…Although the outcome of EMT in the case report by Choi et al (105) was not satisfactory, they suggested that if the EMT is done at early stages, and before the beginning of cortical venous occlusion, the outcome might be better. Therefore, if VITT-associated CVT is clinically suspected and the symptoms deteriorate quickly, early EMT intervention is necessary (105). Another non-pharmacological procedure is decompressive craniectomy, which should be decided based on the patient's condition.…”
Section: Recommendations For Diagnosis and Management Of Cvst After C...mentioning
confidence: 91%
See 1 more Smart Citation
“…Acute transverse myelitis (ATM) has been reported at a higher than expected rate following vaccination with AZD1222 (104). Thrombotic-thrombocytopenia, resultant hemorrhage and sequelae such as ischemic stroke and death have been reported after vaccination with AZD1222 (105,106,107). Gam--COVID--Vac (Sputnik V) is a SARS--CoV--2 viral vector nucleotide vaccine, which utilizes a hybrid approach to viral delivery of a DNA template encoding SARS--CoV--2 spike protein (73,103).…”
Section: Viral Vector Sars-cov-2 Nucleotide Vaccine Candidatesmentioning
confidence: 99%
“…Overall, positive outcomes were reported in no-stroke patients. Advanced endovascular procedures such as rheolysis, flushing, and aspiration with 50% saline solution with contrast medium [49] or mechanical thrombectomy [19] were attempted throughout the jugular vein.…”
Section: Management and Outcomesmentioning
confidence: 99%